OPTIMALISASI MOTIVASI BELAJAR BAHASA MANDARIN MELALUI PEMAHAMAN FILOSOFIS ANALISIS KOMPONEN KARAKTER HÀNZÌ - Adhimas, Yogi Bagus; Amri, Miftachul; Ahmadi, Anas; Dasion, Hans Yosef Tandra; Bahari, Dita Aulia; Swandarta, Safira Firta (Transformasi dan Inovasi : Jurnal Pengabdian Masyarakat, 2024)
Indonesian language has very different characters from Mandarin, such as writing, Indonesian uses the alphabet, and Mandarin uses a character called hànzì. This can make it very difficult for students to learn Mandarin. This difficulty will have an impact on decreasing learning motivation which leads to a decrease in the value of mastering Mandarin of a learner. So in order to shrink the gap between Indonesian language and Mandarin, a cultural approach is used by borrowing one of the uniqueness of Mandarin, namely hànzì. Hànzì which if analyzed its components actually has a deep philosophical meaning. The analysis will reveal how the entire Chinese society in the past, which will more or less be the same as the culture in Indonesia because it is still in one outline of eastern culture. With these cultural similarities, it will be able to touch the hearts of learners, and provide an additional motivational boost in learning Mandarin. In addition, after this understanding is found, memorizing a hànzì will also be easier because the learner can imagine a real-life meaning in the world. More than just a stroke that meets each other which is finally agreed to become a letter called hànzì. After presenting the deep meaning of a hànzì, there was a positive response from the live question and answer dialogue. The increasing enthusiasm of students is also expected to be an effort to optimize Mandarin mastery at SMK 17 Agustus 1945 Surabaya.